Porphyria Cutanea Tarda in a Patient with End-Stage Renal Disease: A Case of Successful Treatment with Deferoxamine and Ferric Carboxymaltose - Natacha Rodrigues; Fernando Caeiro; Alice Santana; Teresa Mendes; Leonor Lopes (Case Reports in Nephrology)
Porphyria cutanea tarda (PCT) is a rare disease, with a strong association with hepatitis C virus. PCT is particularly problematic in end-stage renal disease patients as they have no renal excretion of porphyrins and these are poorly dialyzed. Also, conventional treatment of PCT is compromised in these patients as hydroxychloroquine is contraindicated, phlebotomies with the stipulated frequency are poorly tolerated in already anaemia-prone patients, and iron-chelating agents are less efficient in removing iron and contribute to worsening anaemia. The authors report a patient on haemodialysis, with hepatitis C infection, that is diagnosed with PCT. Despite the good clinical results with deferoxamine, she became dependent on blood transfusions because of her ferropenic state. Every time oxide iron was started, the patient developed clinical features of the disease, resolving after the suspension of the drug. A decision was made to start the patient on ferric carboxymaltose, which was well tolerated without disease symptoms and need of further blood transfusions. This case suggests that deferoxamine is efficient in treatment of porphyria cutanea tarda. Also, ferric carboxymaltose may be a valuable option for refractory anaemia in patients with this disease and end-stage renal disease, as it seems to provide iron without clinical relapse of the disease.